(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This review article presents the materials of domestic and foreign studies on the problem of eliminating the oro-antral communication, and also analyzes the essential views of the concepts and methods of plastic surgery aimed at restoring the tightness of the oral region. Also in this article, the advantages and disadvantages of the illuminated methods are considered in comparison with each other, as well as the long-term results and consequences of various plastic methods are evaluated.